Maximising resilience to sea-level rise in urban coastal ecosystems through systematic conservation planning - Nguyen, Nhung T. H. (2022)
Coastal cities and their natural environments are vulnerable to the impacts of climate change, especially sea-level rise (SLR). Hard coastal defences play a key role in protecting at-risk urban coastal populations from flooding and erosion, but coastal ecosystems also play important roles in the overall sustainability and resilience of cities and urban centres by contributing to coastal protection. Conserving coastal ecosystems and maximising their resilience will ensure that urban coastal communities can continue to benefit from ecosystem services and improve their adaptive capacity to cope with adverse impacts in the future. Using the hyper-urbanised coast of Singapore as a case study, we modelled the resilience of coastal wetlands to SLR and integrated resilience in conservation planning. We found that the responses of coastal habitats to rising sea level vary across the modelling periods. While there is a slight net gain in the extent of mangrove forests and tidal flats by the end of the century due to potential habitat conversion, the existing habitats will experience a loss in coverage. Highly modified coastlines associated with urbanisation impede the ability of existing wetlands to migrate landward, which is a key mechanism for coastal habitats to cope with rising sea levels. Systematic conservation planning can identify sites that are potentially resilient to SLR and incorporate factors that influence an ecosystem's capability to respond to change. Crucially, the relatively slow rates of SLR and persistence of coastal wetlands during the earlier half of this century present an opportunity to introduce management interventions aimed at enhancing ecosystem resilience.